Knowledge of healthcare providers in the management of anaphylaxis - González Díaz, Sandra Nora; Villarreal González, Rosalaura Virginia; Fuentes Lara, Elma Isela; Salinas Díaz, María del Rocío; De Lira Quezada, Cindy Elizabeth; Macouzet Sánchez, Carlos; Macías Weinmann, Alejandra; Guzmán Avilán, Rosa Ivett; García Campa, Mariano (Elsevier Inc., 2021)
Introduction: Anaphylaxis is defined as a severe, life-threatening systemic hypersensitivity reaction. Early diagnosis and treatment of a severe allergic reaction requires recognition of the signs and symptoms, as well as classification of severity. It is a clinical emergency, and healthcare providers should have the knowledge for recognition and management. The aim of the study is to evaluate the level of knowledge in the management of anaphylaxis in healthcare providers. Methods: It is an observational, descriptive, cross-sectional study conducted among healthcare providers over 18 years old via a Google Forms link and shared through different social media platforms. A 12-item questionnaire was applied which included the evaluation of the management of anaphylaxis, from June 2020 to May 2021. Results: A total of 1023 surveys were evaluated; 1013 met inclusion criteria and were included in the statistical analysis. A passing grade was considered with 8 or more correct answers out of 12; the overall approval percentage was 28.7%. The group with the highest percentage of approval in the questionnaire was health-care providers with more than 30 years of work experience. There was a significant difference between the proportions of approval between all specialty groups, and in a post-hoc analysis, allergy and immunology specialists showed greater proportions of approval compared to general medicine practitioners (62.9% vs 25%; p¼<0.001). Conclusions: It is important that healthcare providers know how to recognize, diagnose, and treat anaphylaxis, and later refer them to specialists in Allergy and Clinical Immunology in order to make a personalized diagnosis and treatment.